Treating in-stent restenosis with drug-eluting balloon with intracoronary ultrasound control, with later optical coherent tomography control - Szczepański, Andrzej; Sławin, Janusz; Kübler, Piotr; Jankowska, Ewa A.; Banasiak, Waldemar; Ponikowski, Piotr; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
We present a case report on treating drug eluting stent restenosis with a drug-eluting balloon. In order to recognise the cause of restenosis and to ensure better control of PCI we used intracoronary ultrasound. After three months we confirmed the positive effect of the earlier procedure in the coronary angiography and optical coherent tomography. We discuss the advantages of additional metods of coronary examination and the benefits of using the new device designed for the treatment of in-stent restenosis.